Combination of Three Treatment Modes of 1064 nm Nd: YAG Laser in the Treatment of Melasma: A Retrospective Observational Study - Qiu H; Zhu Y; Wu B; Zhou S; Zhou X; Pan F (Clinical, Cosmetic and Investigational Dermatology)
Houhuang Qiu,1,* Yuyun Zhu,2,* Bingliang Wu,1 Siyuan Zhou,1 Xiang Zhou,1 Fuqiang Pan1 1Department of Medical Cosmetology, Second Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi, People’s Republic of China; 2Department of Medical Cosmetology, Langdong Hospital of Guangxi Medical University, Nanning, Guangxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fuqiang Pan, Department of Medical Cosmetology, Second Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi, People’s Republic of China, Email 42783642@qq.comBackground: Melasma is a chronic, relapsing pigmentary disorder with a high recurrence rate. While multiple treatment options exist, long-term oral therapies are often limited by poor patient tolerance. Laser therapy offers a non-invasive and convenient alternative; however, Low-fluence QS 1064 nm Nd: YAG monotherapy has shown inconsistent efficacy and frequent relapse. To investigate a more effective laser-based approach, this retrospective study evaluates the clinical outcomes of combining Low-fluence QS 1064 nm Nd: YAG laser, Fractional-mode QS 1064 nm Nd: YAG laser, and Long-pulsed 1064 nm Nd: YAG laser in the treatment of melasma.Methods: This retrospective observational study enrolled 43 patients with clinically diagnosed melasma, all of whom underwent treatment with a 1064 nm Nd: YAG laser using a combination of three modes: low-fluence QS, fractional-mode QS, and long-pulsed settings. Each patient underwent a total of three treatment sessions. Clinical improvement was assessed using the MASI at baseline and one month after each session. Adverse events were documented throughout the treatment course. Patients were followed for 12 months post-treatment to evaluate recurrence and satisfaction.Results: MASI scores significantly decreased following the final treatment compared to baseline [13.50 (8.40– 19.10) vs 5.86 ± 3.38, p < 0.001]. At the 12-month follow-up, the recurrence rate was 18.60%, with a patient satisfaction rate of 72.10%. Post-inflammatory hyperpigmentation occurred in 6.97% of cases, and transient erythema or edema in 46.51%, all of which resolved spontaneously.Conclusion: In this retrospective observational study, combination therapy with low-fluence QS 1064 nm Nd: YAG laser, fractional-mode QS 1064 nm Nd: YAG laser, and long-pulsed 1064 nm Nd: YAG laser demonstrated favorable efficacy in the treatment of melasma, with low recurrence rates and a low incidence of adverse events. These findings suggest that this combined laser approach is a promising and well-tolerated treatment modality for melasma.Keywords: melasma, Low-fluence QS 1064 nm Nd: YAG laser, fractional-mode QS 1064 nm Nd: YAG laser, long-pulsed 1064 nm Nd: YAG laser